Impaired myelination and reduced brain ferric iron in the mouse model of mucolipidosis IV - Grishchuk, Yulia (Dis Model Mech, 2015)
Mucolipidosis type IV (MLIV) is a lysosomal storage disease caused by mutations in the MCOLN1 gene, which encodes the lysosomal transient receptor potential ion channel mucolipin-1 (TRPML1). MLIV causes impaired motor and cognitive development, progressive loss of vision and gastric achlorhydria. How loss of TRPML1 leads to severe psychomotor retardation is currently unknown, and there is no therapy for MLIV. White matter abnormalities and a hypoplastic corpus callosum are the major hallmarks of MLIV brain pathology. Here, we report that loss of TRPML1 in mice results in developmental aberrations of brain myelination as a result of deficient maturation and loss of oligodendrocytes. Defective myelination is evident in Mcoln1(−/−) mice at postnatal day 10, an active stage of postnatal myelination in the mouse brain. Expression of mature oligodendrocyte markers is reduced in Mcoln1(−/−) mice at postnatal day 10 and remains lower throughout the course of the disease. We observed reduced Perls' staining in Mcoln1(−/−) brain, indicating lower levels of ferric iron. Total iron content in unperfused brain is not significantly different between Mcoln1(−/−) and wild-type littermate mice, suggesting that the observed maturation delay or loss of oligodendrocytes might be caused by impaired iron handling, rather than by global iron deficiency. Overall, these data emphasize a developmental rather than a degenerative disease course in MLIV, and suggest that there should be a stronger focus on oligodendrocyte maturation and survival to better understand MLIV pathogenesis and aid treatment development.